Democratization of Expertise: How Cognitive Systems Will Revolutionize Your Life - Fulbright, Ron (CRC Press, 2020)
This book discusses societal and cultural revolutions throughout history brought about by the adoption of new technology and gives brief histories of human cognitive augmentation and artificial intelligence. In the coming cognitive systems era, humans, by collaboratively partnering with cognitive systems, will together achieve expert-level performance—synthetic expertise—with humans performing some of the cognitive processing and cognitive systems performing some. As the capabilities of cognitive systems improve over time, the balance of thinking will shift from being mostly human to mostly artificial. This book introduces the Levels of Cognitive Augmentation to describe this shift. Drawing from previous research in cognitive systems and intelligent agent theory, the knowledge stores required for expertise are identified in a Knowledge Level description of expertise. This book introduces a new abstract level, called the Expertise Level to describe the skills needed for expertise. Combining the knowledge-level and expertise-level descriptions, this book introduces the Model of Expertise. This book demonstrates use of the Model of Expertise by presenting several synthetic expert architectures: a synthetic teacher (Synthia), a synthetic friend/therapist (Sy), a synthetic elderly companion (Lois), a synthetic research companion (Synclair), and an automated scientific hypothesis explorer (Ashe). This book is intended for anyone interested in the fields of cognitive systems, cognitive computing, cognitive augmentation, or artificial intelligence or the impact of technologies from these fields on society. Anyone doing research and development in the area of cognitive systems or artificial intelligence will find this book particularly useful.